Straits Settlements Blue Book (imports/exports) 1921-1923 vol.73-75 (Great Britain : Public Record Office, 1971)
Mengandungi sambungan kepada'Blue Book for the year 1921';'Blue Book for the year 1922';'Blue Book for the year 1923'.